Disjunction in Negative Contexts: A Cross-Linguistic Experimental Study. (18th May 2021) - Lungu, Oana; Fălăuș, Anamaria; Panzeri, Francesca
Abstract: This squib reports experimental findings from a study investigating the interpretation of simple disjunction in negative contexts in four languages: Italian, French, English, Romanian. We provide evidence that casts doubt on the robustness of the distinction between PPI disjunction languages and non-PPI disjunction languages. The difference turns out to be less clear-cut than assumed in the theoretical (e.g., Szabolcsi 2002, Spector 2014, Nicolae 2017 ) or experimental literature (e.g., Crain 2012, Guasti et al. 2017 ). The results reported here inform current accounts of positive polarity and flesh out some methodological issues raised by the various tasks used in experimental investigations of the polarity sensitivity of disjunction.